Inclusive and gender-transformative seed systems: Concepts and applications - Galiè, Alessandra; Kramer, Berber; Spielman, David J.; Kawarazuka, Nozomi; Rietveld, Anne M.; Aju, Stellamaris (Elsevier, 2025)
CONTEXT Seed is vital to the nutrition and livelihoods of millions of women and men small-scale farmers in low- and middle-income countries. Seed systems interventions can significantly enhance food security and nutrition by accelerating the adoption of improved varieties and the use of quality seed, which in turn increase the rate of genetic gain, productivity, and household welfare. These interventions can be particularly effective when advancing gender equality by supporting women's empowerment and addressing discriminatory gender norms. However, there is relatively little evidence on the ways in which seed systems can be an entry point for advancing gender equality by transforming discriminatory gender norms. OBJECTIVES We develop and illustrate a gender transformative approach applied to seed sector development. Our first objective is to provide a framework to better understand how seed systems interventions can contribute to gender equality by (1) integrating gender-accommodative and gender-transformative approaches; and (2) assessing their gendered impacts. Our second objective is to apply this framework to a particular innovation – gender messaging via information and communications technologies (ICTs) – and explore how seed system interventions can be made more gender-transformative. METHODS We first reviewed the existing literature to develop a framework that defines gender-transformative and accommodative seed system interventions and their impacts. We then synthesized lessons learned from the application of this framework to case studies from Ethiopia, Kenya, Tanzania, and Uganda that used ICTs that contained gendered components. RESULTS AND CONCLUSION We discuss how a gender-accommodative approach aims for gender considerations to improve seed systems, while a gender-transformative approach flips the goal around by aiming at progress toward gender equality through seed systems. We find growing evidence on the potential of gender-transformative seed systems interventions to influence positively the empowerment of women and also men, and to create more conducive gender norms, as shown by three case studies on ICT enablers. These case studies also show that accommodative and transformative approaches are often complementary. SIGNIFICANCE We introduce research questions that research and development practitioners can ask to develop accommodative or transformative approaches in seed system interventions, and show the potential of both approaches to progress toward gender equality. The case studies indicate the feasibility of gender-transformative, ICT-enabled seed system interventions, with clear indications of the potential for low-cost adaptation at scale. However, the transformative potential of these interventions requires careful consideration of messaging content, format, and context, as well as strategic public investment and strong political will.